Prenatal Alcohol Exposure in Rodents As a Promising Model for the Study of ADHD Molecular Basis - Rojas-Mayorquín, Argelia E.; Padilla-Velarde, Edgar; Ortuño-Sahagún, Daniel (Frontiers in Neuroscience, 2016)
A physiological parallelism, or even a causal effect relationship, can be deducted from the analysis of the main characteristics of the “Alcohol Related Neurodevelopmental Disorders” (ARND), derived from prenatal alcohol exposure (PAE), and the behavioral performance in the Attention-deficit/hyperactivity disorder (ADHD). These two clinically distinct disease entities, exhibits many common features. They affect neurological shared pathways, and also related neurotransmitter systems. We briefly review here these parallelism, with their common and uncommon characteristics, and with an emphasis in the subjacent molecular mechanisms of the behavioral manifestations, that lead us to propose that PAE in rats can be considered as a suitable model for the study of ADHD.